Pengaruh Kepemimpinan Transformasional, Budaya Organisasi dan Komitmen Organisasi Terhadap Employe Engagement pada Lembaga Pembinaan Khusus Anak Kelas II Manokwari - Jalmav, Desy Maria; Hattab, Syahruddin; Milwan, Milwan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The success of an organization or institution is highly dependent on the performance and involvement of employees in carrying out their duties. One of the main factors that can improve employee performance is employee engagement, which reflects the level of engagement, commitment, and enthusiasm of employees at work. There are several variables that can be used as factors that affect employee engagement, namely transformational leadership, organizational culture, and organizational commitment. This study aims to find out how the influence of transformational leadership, organizational culture, and organizational commitment on employee engagement at the Manokwari Class II Special Children's Development Institution. This type of research is a quantitative research with an explanatory approach, with a total of 47 respondents. The research method used is a survey with the collection of primary data through questionnaires and secondary data from various related sources. Data analysis was carried out using Validity Test, Reliability Test, Multiple Regression Analysis, Determination Coefficient Analysis (R2), t-Test, F-Test, and then the data was analyzed using SPSS 29.0. The results of the study showed that transformational leadership had no effect on employee engagement, from the results of the t-test a t-count value of 1,126, while a t-table value of 1,679 was obtained. Organizational culture affects employee engagement, the results of the t-test obtained a t-count value of 2,319, while a t-table value obtained a value of 1,679. Organizational commitment has no effect on employee engagement, the t-test results obtained a t-count value of 0.552, while the t-table value obtained a value of 1.679. From the results of the research that has been tested, the Manokwari Class II Special Children's Development Institution can strengthen Transformational Leadership, develop organizational culture, and increase organizational commitment so that employee engagement in the institution can be increased.